A status of guinea fowl (Numida meleagris) and pheasant (Phasianus colchicus) population transferred from wildlife to the breeding assessed based on the histone H1.c' polymorphic variation. Issue 4 (November 2019) - Kowalski, Andrzej
The genetic changes accompanying a relocation of population to the captivity are mostly adverse and usually associated with deterioration of its status. These alterations are greater in small populations in which a loss of genetic variation limits the capability to adaptation. In this work, a status of small-sized guinea fowl and pheasant population relocated to the breeding is presented. These populations were analyzed based on the polymorphism of histone H1.c', the protein for the first time identified as a heterogeneous. Histone H1.c' was resolved in the two-dimensional polyacrylamide gel into the isoform H1.c'1 and H1.c'2, so its heterogeneity corresponds to the presence of homozygous phenotypes c'1 and c'2. Because no histone H1.c' heterozygous phenotype was found, a significant phenotypic diversity in the guinea fowl ( P = 0.023) and pheasant ( P = 0.018) population was detected, together with its departures from Hardy-Weinberg equilibrium ( P < 0.0001). Both populations characterize an extreme loss of genetic diversity due to complete inbreeding ( F = 1) and an impact of genetic drift which, according to the expected values for guinea fowl (0.192) and pheasant (0.182) population, may strongly diminish allele frequency in the following generations. Thus, condition of populations evaluated based on the histone H1.c' polymorphic variants, recognized as reasonable informative genetic markers (polymorphism information content of guinea fowl = 0.4 and pheasant = 0.38), corresponds to reduction of genetic variability caused by inbreeding and genetic drift. Therefore, it seems that rearing in the captivity can bring negative effects that favor restriction of animals' vitality and survival of the population.